(untitled) (Journal of Contemporary Educational Policies and Practices, 2024)
Project based learning (PBL) has been increasingly recognized as an effective approach to enhance teacher professional development, fostering innovative teaching practices and student-centered learning environments. This study investigates the integration of PBL in Vietnamese kindergartens and its influence on teacher professional development. Employing the new teacher professional development framework, the research initially conducted a questionnaire survey with 272 preschool teachers nationwide, followed by in-depth interviews with 11 teachers. The study examines the motivations behind PBL adoption, the implementation process, challenges encountered, and the effectiveness of PBL compared to traditional teaching methods. Through these data collection methods, the research reveals that PBL offers significant opportunities for professional growth and development, including enhanced pedagogical skills, increased student engagement, and a more learner-centered approach. Despite challenges such as limited resources and a lack of familiarity with PBL, teachers reported positive experiences and a willingness to continue integrating PBL into their classrooms.